2017
DOI: 10.1186/s12967-017-1242-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Intra-articular injection in the knee of adipose derived stromal cells (stromal vascular fraction) and platelet rich plasma for osteoarthritis

Abstract: BackgroundStromal vascular fraction (SVF) can easily be obtained from a mini-lipoaspirate procedure of fat tissue and platelet rich plasma (PRP) can be obtained from peripheral blood. We evaluated the safety and preliminary efficacy of administering SVF and PRP intra-articularly into patients with osteoarthritis grade 1 and 2.MethodsA total of ten patients underwent a local tumescent liposuction procedure to remove approximately 100 ml of fat tissue from the abdomen. SVF was isolated using an enzyme digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 31 publications
2
85
0
Order By: Relevance
“…In particular, increased action of the matrix metalloproteinases (MMPs) in combination with reduction of their inhibitors (TIMPs) levels are largely responsible for the earliest osteoarthritic changes [60], suggesting that a restoration of the healthy balance would help in residual cartilage protection and regeneration. Interestingly, in pioneering studies on OA patients, SVF injection was able to stimulate partial regeneration of the articular cartilage, as described by positive changes in the imaging outcomes (MRI or CT) [61][62][63][64][65]. Consistently, in the last years, few clinical trials based on intra-articular injection of autologous ASCs in OA joints reported improvement in pain, function and cartilage volume [66,67].…”
Section: Discussionmentioning
confidence: 92%
“…In particular, increased action of the matrix metalloproteinases (MMPs) in combination with reduction of their inhibitors (TIMPs) levels are largely responsible for the earliest osteoarthritic changes [60], suggesting that a restoration of the healthy balance would help in residual cartilage protection and regeneration. Interestingly, in pioneering studies on OA patients, SVF injection was able to stimulate partial regeneration of the articular cartilage, as described by positive changes in the imaging outcomes (MRI or CT) [61][62][63][64][65]. Consistently, in the last years, few clinical trials based on intra-articular injection of autologous ASCs in OA joints reported improvement in pain, function and cartilage volume [66,67].…”
Section: Discussionmentioning
confidence: 92%
“…In summary, there are no level I studies evaluating micro-fragmented adipose tissue for musculoskeletal disorders. The only randomized studies currently available evaluate the stromal vascular fraction or the culture-expanded adipose-derived product, which are not currently approved for use in orthopedic applications in the United States (Table 4) [132][133][134][135][136][137][138][139][140].…”
Section: Specific Clinical Applicationsmentioning
confidence: 99%
“…Comella et al reported on the safety of SVF in a variety of indications with various delivery methods. Other publications have demonstrated success of SVF for specific conditions including: chronic obstructive pulmonary disease (COPD) [17], congestive heart failure [18], degenerative disc disease [19], osteoarthritis/orthopedics [20][21][22][23][24], radiation necrosis [25], sclerosis [26], tendinopathy [27], xerostomia [28], psoriasis [29] and multiple sclerosis [30]. The following is a case report and to our knowledge first in man a single injection of SVF and PRP into a chronic non-healing stage 3 ulcer in a patient with an incomplete spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%